Impact of genomic alterations on lapatinib treatment outcome and cell-free genomic landscape during HER2 therapy in HER2+ gastric cancer patients. (2nd February 2018) - Kim, S T; Banks, K C; Pectasides, E; Kim, S Y; Kim, K; Lanman, R B; Talasaz, A; An, J; Choi, M G; Lee, J H; Sohn, T S; Bae, J M; et al.
Abstract: Background: To identify predictive markers for responders in lapatinib-treated patients and to demonstrate molecular changes during lapatinib treatment via cell-free genomics. Patients and methods: We prospectively evaluated the efficacy of combining lapatinib with capecitabine and oxaliplatin as first line neoadjuvant therapy in patients with previously untreated, HER2-overexpressing advanced gastric cancer. A parallel biomarker study was conducted by simultaneously performing immunohistochemistry and next-generation sequencing (NGS) with tumor and blood samples. Results: Complete response was confirmed in 7/32 patients (21.8%), 2 of whom received radical surgery with pathologic-confirmed complete response. Fifteen partial responses (46.8%) were observed, resulting in a 68.6% overall response rate. NGS of the 16 tumor specimens demonstrated that the most common co-occurring copy number alteration was CCNE1 amplification, which was present in 40% of HER2+ tumors. The relationship between CCNE1 amplification and lack of response to HER2-targeted therapy trended toward statistical significance (66.7% of non-responders versus 22.2% of responders harbored CCNE1 amplification; P  = 0.08). Patients with high level ERBB2 amplification by NGS were more likely to respond to therapy, compared with patients with low level ERBB2 amplification ( P  = 0.02). Analysis of cfDNA showed that detectable ERBB2 copy number amplification in plasma was predictive to the response (100%, response rate) and changes in plasma-detected genomic alterations were associated with lapatinib sensitivity and/or resistance. The follow-up cfDNA genomics at disease progression demonstrated that there are emergences of other genomic aberrations such as MYC, EGFR, FGFR2 and MET amplifications. Conclusions: The present study showed that HER2+ GC patients respond differently according to concomitant genomic aberrations beyond ERBB2, high ERBB2 amplification by NGS or cfDNA can be a positive predictor for patient selection, and tumor genomic alterations change significantly during targeted agent therapy.